1987
DOI: 10.1042/bj2450119
|View full text |Cite
|
Sign up to set email alerts
|

Phospholipid synthesis in isolated alveolar type II cells exposed in vitro to paraquat and hyperoxia

Abstract: Isolated alveolar epithelial type II cells were exposed to paraquat and to hyperoxia by gas diffusion through the thin Teflon bottom of culture dishes. After exposure, type II cells were further incubated in the presence of labelled substrates to assess their capacity to synthesize lipids. Hyperoxia alone (90% O2; 5 h) had minor effects on lipid metabolism in the type II cells. At low paraquat concentrations (5 and 10 microM), hyperoxia enhanced the paraquat-induced decrease of [Me-14C]choline incorporation in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

1989
1989
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 25 publications
(3 reference statements)
0
5
0
Order By: Relevance
“…These proliferating type II cells have a decreased lamellar body pool size (19), which is consistent with a decreased synthesis of surfactant. Second, production or secretion of phospholipids and SP-A by type II cells can be impaired by reactive oxygen metabolites and cytokines (20)(21)(22)(23), which are generated after lung transplantation (24,25). Both these mechanisms may have induced the changes of surfactant that we measured at 1 wk after the initial transplantation injury in the present study.…”
Section: Discussionmentioning
confidence: 74%
“…These proliferating type II cells have a decreased lamellar body pool size (19), which is consistent with a decreased synthesis of surfactant. Second, production or secretion of phospholipids and SP-A by type II cells can be impaired by reactive oxygen metabolites and cytokines (20)(21)(22)(23), which are generated after lung transplantation (24,25). Both these mechanisms may have induced the changes of surfactant that we measured at 1 wk after the initial transplantation injury in the present study.…”
Section: Discussionmentioning
confidence: 74%
“…These proliferating type II cells have a decreased lamellar body pool size (19) which is consistent with a decreased synthesis of surfactant. Second, production or secretion of phospholipids and SP-A by type II cells can be impaired by reactive oxygen metabolites and cytokines (20)(21)(22)(23) which are generated after lung transplantation (24,25). Both these mechanisms may have induced the changes of surfactant that we measured at one week after the initial transplantation injury in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…The remainder of BALF was centrifuged overnight at 100,000 g, 4 o C, to concentrate the surfactant in a pellet (P3) for the determination of the phospholipid-composition. The phospholipids were separated by thin layer chromatography according to Touchstone and coworkers (20) with the use of their solvent E .The amount of SP-A was assessed in BALF with a sandwich ELISA method (21). The measured amounts of SP-A do represent endogenous SP-A of the lung transplants, since the surfactant used did not contain SP-A.…”
Section: Components Of Alveolar Surfactantmentioning
confidence: 99%
“…Previous studies have demonstrated that apoptosis is an important process in injured to the lung epithelium in paraquat (PQ) poisoning ( 1 , 2 ). The mechanisms of apoptosis are highly complex and involve oxidative/nitrative stress impairment to the function of mitochondria with the reduction of the mitochondrial membrane potential (ΔΨ), resulting in an increase of superoxide formation and reduced production of adenosine 5′-triphosphate (ATP) ( 3 , 4 ). Previous studies suggest that adenosine 5′-monophosphate-activated protein kinase (AMPK) is one of the most important molecules in the stimulation of ATP production and protection against oxidative/nitrative stress in mitochondria ( 5 , 6 ).…”
Section: Introductionmentioning
confidence: 99%